Static analysis of the cylindrical tank resting on various types of subsoil - Mistríková, Zora; Jendželovský, Norbert (Journal of Civil Engineering and Management, 2012)
The paper presents analyses of deformations and stress of the circular rotationally symmetric tanks. The reinforced concrete tanks – water reservoirs – resting on elastic subsoil have been analyzed. The elastic subsoil has been modeled using three basic subsoil models: half-space model, two-parametric model and one-parametric (Winkler) subsoil model. Particular modifications have been applied to the basic models which yield in seven models presented. The cylindrical tank has been analyzed in the interaction with the subsoil, while the elastic subsoil has been characterized by different parameters. The differences in modeling using individual calculation models have been highlighted. The results from analytical and numerical solutions have been presented and compared in graphs and tables. The method for the calculation of settlement of the circular foundation plate was verified experimentally. The settlement of the circular plate was measured while the silo was fully loaded by its contents. The experimentally obtained values have been compared with the calculation results. In the conclusion the recommendations for the suitable model subsoil for these types of structures have been presented.